Perancangan Rumah Sakit Kelas D Nani Wartabone Di Kabupeten Bone Bolango Dengan Pendektan Arsitektur Tropis - Adriansyah Lolonto; Nurnaningsih Nico Abdul; Mohamad Faisal Dunggio (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Hospitals are healthcare facilities that provide comprehensive individual health services, including inpatient, outpatient, and emergency care, as regulated by the Regulation of the Minister of Health of the Republic of Indonesia Number 4 of 2018. Along with growing public awareness, sustainability in healthcare services has become a critical issue that must be addressed. Bone Bolango Regency has two government hospitals, namely Toto Kabila Regional Hospital and Tombulilato Regional Hospital. However, these facilities have not adequately served communities located far from the hospital areas, such as Botupingge, Suwawa, South Suwawa, East Suwawa, Central Suwawa, and Pinogu Districts. The long travel distance—approximately 35 km from East Suwawa to Toto Kabila Hospital—poses a significant barrier for residents in accessing proper healthcare services. Therefore, the development of a new hospital is necessary to support healthcare services for seven districts in Bone Bolango Regency. The proposed hospital is expected to be environmentally friendly and equipped with adequate facilities while responding to the region’s hot tropical climate. Design strategies include optimizing natural lighting, cross ventilation, and protection from solar heat and rainfall. This study employs primary and secondary data collected from various sources and previous studies, analyzed using a qualitative descriptive method. The collected data are then transformed into design concepts. A tropical architecture approach is applied to create a comfortable, healthy, and climate-responsive healing environment, while emphasizing energy efficiency and sustainable use of natural resources.